RANCANG BANGUN APLIKASI REKAP DATA AMPRAHAN BERBASIS WEB DENGAN METODE WATERFALL DI PT LINTAS BAHARI NUSANTARA - Alfiyan Anwar; Suhanda Saputra; Khoirunnisya (CV. Multi Kreasi Media, 2023)
PT Lintas Bahari Nusantara or abbreviated as LBN is a company engaged in shipping. PT. LBN provides cargo/goods transportation services for cities in Indonesia with several fleets that transport goods by sea. Every delivery of customer goods by people on the ship will definitely make a list of requests for needs or what is commonly called amrahan for needs on the ship. Currently, the system for recording shipments of goods supplied to ships only uses travel documents written on a piece of paper and photos of travel documents which are shared with the operational group. This makes work inefficient. If there is a problem with lost goods, you have to check the data on the delivery of goods through a physical delivery document or search for photos of a travel document that has been photographed and shared with the operational group each time it is sent. This research was conducted to help make it easier to recap data on the delivery of goods supplied to ships, and also to help make it easier to check what date the missing goods have been sent quickly. This study uses the waterfall method. Data collection methods used to collect data in this study are observation and interviews. This system is designed with the PHP programming language, the Laravel framework, the filament admin panel and uses the MySQL database.